ANALISIS PENGARUH DIFERENSIASI, PROMOSI DAN POSITIONING TERHADAP KEPUTUSAN PEMBELIAN (Studi pada Pelanggan Sepeda Motor Merek Honda di Kota Tangerang) - Abdul Rauf (JMB : Jurnal Manajemen dan Bisnis, 2018)
The purpose of the study is to analyze how much influencedifferentiation, promotion and positioning on purchase decision ofHonda motorcycles customers. The sample of research is 100 Hondamotorcycles customers in Tangerang. The sampling technique usesconvenience sampling. Data collection using questionnaire. The methodused in this research is the method of verification to determine theeffect of differentiation, promotion and positioning on purchase decision.The test statistic used is designing the structural model, designing ameasurement model, construct the path diagram, test the model fit.Suitability test structural models and hypotheses using software LISREL8.80. The results showed that differentiation and promotion have asignificant effect on customer satisfaction, whereas positioning have nosignificant effect on purchase decision.